Prognostic nutrition index predicts short-term surgical complications in patients with rectal cancer after laparoscopic surgery - Xu, Fengming; Meng, Cong; Yang, Zhengyang; Li, Haoze; Gao, Jiale; Sun, Liting; Zhang, Xiao; Wei, Qi; Wu, Guocong; Yao, Hongwei; Zhang, Zhongtao (Frontiers in Surgery, 2022)
Purpose Surgical complications following laparoscopic rectal cancer surgery remain a major clinical problem. The prognostic nutritional index (PNI) is reportedly associated with postoperative outcomes. We aimed to evaluate the correlation between PNI and short-term surgical complications in patients with rectal cancer after laparoscopic surgery. Methods The prospective clinical data of 225 patients with rectal cancer receiving laparoscopic surgery between January 2021 and April 2022 were retrospectively analyzed. The cut-off values and diagnostic accuracy of PNI preoperatively and on postoperative day (POD) 1 were determined using receiver operating characteristic (ROC) curves. Univariate and multivariate analyses were performed to identify clinical characteristics and risk factors for surgical complications. Results In total, 81 (36.0%) patients developed surgical complications. The optimal cut-off value for preoperative PNI was 40.15, and that for PNI on POD 1 was 35.28. The DeLong test found no statistically between–group difference in the area under the ROC curve (P = 0.598). Multivariate analysis identified that a preoperative PNI ≤40.15 [odds ratio (OR): 2.856, 95% confidence interval (CI): 1.287–6.341, P = 0.010] and PNI on POD 1 ≤35.28 (OR: 2.773, 95% CI: 1.533–5.016, P = 0.001) were independent risk factors for surgical complications. Patients with a preoperative PNI ≤40.15 or PNI on POD 1 ≤35.28 were more likely to have surgical complications after laparoscopic surgery for rectal cancer (61.1% vs. 31.2%, P = 0.001; 53.0% vs. 28.9%, P = 0.001). Conclusion Preoperative and POD 1 PNI were independent predictors of short-term surgical complications after laparoscopic surgery for rectal cancer.